Microbial cell wall sorption and Fe–Mn binding in rhizosphere contribute to the obstruction of cadmium from soil to rice - Li, Jie; Guo, Yi-Kai; Zhao, Qing-Xia; He, Ji-Zheng; Zhang, Qian; Cao, Hong-Ying; Liang, Chao-Qiong (Frontiers in Microbiology, 2023)
Screening high tolerant microorganisms to Cadmium (Cd) and revealing their bio-obstruction mechanism could be significant for Cd regulation from farmland to food chain. We examined the tolerance and bio-removal efficiency of Cd ions of two bacterial strains Pseudomonas putida 23483 and Bacillus sp. GY16, and measured the accumulation of Cd ions in rice tissues and its different chemical forms in soil. The results showed that the two strains had high tolerance to Cd, but the removal efficiency was decreased successively with increasing Cd concentrations (0.05, 0.5, 5 mg kg-1). Cell-sorption accounted for the major proportion of Cd removing compared to excreta binding in both strains, which was conformed to the Pseudo-second-order kinetics. At the subcellular level, Cd was mostly taken up by cell mantle and cell wall, and only a small amount entered into cytomembrane and cytoplasmic with time progressed (0 – 24 h) in each concentration. The cell mantle and cell wall sorption decreased with increasing Cd concentration, especially in cytomembrane and cytoplasmic. The Scanning Electron Microscope (SEM) and Energy Dispersive X-ray (EDS) analysis verified that Cd ions were attached to cell surface, and the functional groups of C-H, C-N, C=O, N-H and O-H in cell surface may participate in cell sorption process tested by FTIR analysis. Furthermore, inoculation of the two strains significantly decreased Cd accumulation in rice straw and grain but increased in root, increased the enrichment ratio of Cd in root from soil whereas decreased the translocation ratio of Cd from root to straw and grain, and increased the Cd concentrations of Fe-Mn binding form and residual form in rhizosphere soil. This study highlights that the two strains mainly removed Cd ions in solution through bio-sorption, and passivated soil Cd as Fe-Mn combined form ascribe to its characteristics of manganese oxidizing, eventually achieved bio-obstruction of Cd from soil to rice grain.